Study of Some Biochemical and Blood Parameters as Screening Markers for Breast Cancer Patients before Adjuvant Therapy in Thi Qar Government-Southern Iraq - Jamal Harbi Hussein Alsaadi (Journal of Global Pharma Technology, 2019)
Breast cancer is the most common malignancy disease in women. The study includes Eighty-three  cases were divided according age into women (patients and healthy ) average age more than forty five( Age > 45 year)   Fifty - five confirmed  subject of breast cancer patients (n = 42), healthy as control group (n=18) and women (patients and healthy) average age less than forty five Age (< 45 year) twenty three distributed to(2) groups too  .The first  group  confirmed (n=13)cases of breast cancer patients  and  second group (n=10)as control group. They were evaluated for blood parameters and some biochemical parameters that are associated with breast cancer occurring in Thi-Qar Government .Iraq. study has revealed that  significant decreasing (p<0.001) observed in  HB , PCV, RBC  and  WBC   levels  and a significant increasing  (P < 0.05) Platelets   , ESR   and  Monocyte retrospectively  in cancer patients comparison to normal control subjects and significant correlation (P< 0.05) between Neutrophil and Lymphocyte  , rates of NLR and PLR were significantly higher in breast cancer patients compared to control group   at  Age  > 45 year .While  the results showed for women   mean Age (< 45 year). The mean haemoglobin (Hb) , packed cell volume( PCV)  and  Red blood cells  (RBC) levels in the patient group were a significantly and lower than the control group at (p>0.05). There was high significant differences in WBCs   neutrophils, lymphocytes, monocytes also significant difference ESR (p>0.01) compared with healthy female .The values of NLR and PLR were showed significantly but no high   in the patients compare   with   healthy group. In this study  biochemical Parameters(lipid profile ) ,were showed  a significant decreasing at (p>0.01) for ;lipid profile parameters (Cholesterol, T.G, HDL and LDL) compared with  biochemical Parameters measurement  values of  female control mean  Age  > 45 year , while results showed  that significant increasing at (p>0.05)in  some lipid profiles in breast cancer patients compared with healthy control group  in women Age (<45 year).Keywords: Breast cancer, Lipid profile, Blood Parameters.